2005
DOI: 10.1128/aem.71.12.8846-8854.2005
|View full text |Cite
|
Sign up to set email alerts
|

Highly Divergent Genes for Methanopterin-Linked C 1 Transfer Reactions in Lake Washington, Assessed via Metagenomic Analysis and mRNA Detection

Abstract: The origins and the evolutionary history of tetrahydromethanopterin-linked C 1 transfer reactions that are part of two environmentally important biotransformations, methylotrophy and methanogenesis, are still not well understood. In previous studies, we have expanded the known phylogenetic diversity of these reactions by identifying genes highly diverging from the ones associated with cultivated Proteobacteria, Planctomycetes, or Archaea ( Here we used a metagenomic approach to demonstrate that these divergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Lake Washington sediment core samples were collected as described previously (Kalyuzhnaya et al, 2005b). Sediment cores were transported to the laboratory on ice and stored at 4 1C.…”
Section: Bacterial Cultures and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lake Washington sediment core samples were collected as described previously (Kalyuzhnaya et al, 2005b). Sediment cores were transported to the laboratory on ice and stored at 4 1C.…”
Section: Bacterial Cultures and Growth Conditionsmentioning
confidence: 99%
“…The upper layer of the sediment of this lake is known for high rates of methane metabolism and is an attractive model for studying environmental cycling of C 1 compounds. The C 1 -utilizing bacterial community has been characterized so far using a number of culture-reliant (Auman et al, 2000;Miller et al, 2005;Kalyuzhnaya et al, 2005aKalyuzhnaya et al, , 2006a) and culture-independent methods, including surveys of functional genes, detection of specific RNA transcripts and stable isotope probing (Costello and Lidstrom, 1999;Kalyuzhnaya et al, 2005b;Nercessian et al, 2005). The picture emerging from these studies shows a complex multimember community that includes species known for methylotrophic capability (Methylomonas, Methylobacter, Methylocystis, Methyloversatilis, Methylotenera etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment samples were collected on 3 March 2009 and on 27 July 2009 as described previously (9). Sediment cores were transported to the laboratory on ice and stored at 9°C.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this helps in identification of cells involved in a targeted metabolic process. We used methanol as an example of a single-carbon compound for detection of methylotrophic abilities among bacterial populations from the well-studied sediment of Lake Washington in Washington (2,3,(8)(9)(10)(11) and demonstrated that it is possible to use RRI for direct functional profiling of environmental samples.…”
mentioning
confidence: 99%